M-learning programming platform: Evaluation in elementary schools - Alepis, Efthimios; Troussas, Christos (Informatica, 2017)
Mobile learning has invaded the everyday life and therefore evaluation methodology and reporting should be used so that mobile technologies are tested out in a variety of learning contexts. Το this direction, a mobile learning platform, named m-AFOL, was designed for elementary school students so that they are taught basic programming principles. The platform is a sophisticated learning tool that incorporates affective interaction among learners and tutoring agents in order to maximize educational gains. The paper presents a two-level evaluation study of m-AFOL, estimating its effectiveness and acceptance rate. The evaluation concludes that the mobile facilities of the resulting intelligent tutoring system are highly acceptable (over 80%) from young learners, being keen on using mobile devices while learning. Concluding. the mobile platform is evaluated in comparison with a desktop version of resulting system.